PENGARUH FDR, NPF DAN BOPO TERHADAP ROA PERBANKAN SYARIAH DI INDONESIA - Alif Rana Fadhilah; Noven Suprayogi (Universitas Airlangga, 2019)
The purpose of this study is to determine the effect of the Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Operational Cost variable to Operational Revenue (BOPO) toward Return On Asset (ROA) at Islamic Bank in Indonesia period 2013-2017 partially and simultaneously. This study uses a quantitative approach. Samples were determined using purposive sampling technique and the number of selected samples was 13 Islamic Commercial Banks. This study uses regression analysis with panel data tests to determine the relationship between exogenous variables and endogenous variables. The result of this research shows that BOPO is partially has significant influence to the profitability . Meanwhile, FDR and NPF are partially have insignificant influence to the profitability. While simultaneously, FDR, NPF and BOPO have significant influence to the profitability of Islamic bank with the coefficient of determination is 80,48% while the remaining 19,52% is influenced by other variables not included in this research.Keywords: ROA, FDR, NPF, BOPO and Islamic Bank